Systematic uncertainties from halo asphericity in dark matter searches - Bernal, Nicolas [UNESP]; Forero-Romero, Jaime E.; Garani, Raghuveer; Palomares-Ruiz, Sergio (Iop Publishing Ltd, 2014)
Although commonly assumed to be spherical, dark matter halos are predicted to be non-spherical by N-body simulations and their asphericity has a potential impact on the systematic uncertainties in dark matter searches. The evaluation of these uncertainties is the main aim of this work, where we study the impact of aspherical dark matter density distributions in Milky-Way-like halos on direct and indirect searches. Using data from the large N-body cosmological simulation Bolshoi, we perform a statistical analysis and quantify the systematic uncertainties on the determination of local dark matter density and the so-called J factors for dark matter annihilations and decays from the galactic center. We find that, due to our ignorance about the extent of the non-sphericity of the Milky Way dark matter halo, systematic uncertainties can be as large as 35%, within the 95% most probable region, for a spherically averaged value for the local density of 0.3-0.4 GeV/cm(3). Similarly, systematic uncertainties on the J factors evaluated around the galactic center can be as large as 10% and 15%, within the 95% most probable region, for dark matter annihilations and decays, respectively.
Keywords: dark matter theory; dark matter simulations